2017
DOI: 10.1016/j.physletb.2017.08.073
|View full text |Cite
|
Sign up to set email alerts
|

Integrability and chemical potential in the (3 + 1)-dimensional Skyrme model

Abstract: Using a remarkable mapping from the original (3+1)dimensional Skyrme model to the Sine-Gordon model, we construct the first analytic examples of Skyrmions as well as of Skyrmions-anti-Skyrmions bound states within a finite box in 3+1 dimensional flat space-time. An analytic upper bound on the number of these Skyrmions-anti-Skyrmions bound states is derived. We compute the critical isospin chemical potential beyond which these Skyrmions cease to exist. With these tools, we also construct topologically protected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(105 citation statements)
references
References 69 publications
3
102
0
Order By: Relevance
“…where H ∈ [0, π/2], while A ∈ [0, 2πk 1 ], G ∈ [0, 2πk 2 ] are both periodic Killing coordinates of S 3 , with k 1 and k 2 positive integers (there is clearly some redundancy in this choice of the periodicities -the standard choice k 1 = k 2 = 1 already covers the whole S 3 -but this will become physically meaningful later on). In [19] and [25] it has been shown that similar parametrizations are extremely useful both in curved and in flat spaces. The tensor S µν (11) takes the form…”
Section: The Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…where H ∈ [0, π/2], while A ∈ [0, 2πk 1 ], G ∈ [0, 2πk 2 ] are both periodic Killing coordinates of S 3 , with k 1 and k 2 positive integers (there is clearly some redundancy in this choice of the periodicities -the standard choice k 1 = k 2 = 1 already covers the whole S 3 -but this will become physically meaningful later on). In [19] and [25] it has been shown that similar parametrizations are extremely useful both in curved and in flat spaces. The tensor S µν (11) takes the form…”
Section: The Actionmentioning
confidence: 99%
“…However, the recent generalization of the boson star ansatz to SU (2)-valued scalar fields (introduced in [12][13][14][15][16][17][18][19][20][21][22] and [23][24][25]) allows to construct also non-trivial gravitating soliton solutions (see in particular [13] and [19]) as well as to analyse explicitly thermodynamic properties of solitons (see [25]).…”
Section: Introductionmentioning
confidence: 99%
“…Time crystals are quantum systems where a crystalline structure emerges in time with no initial crystalline structure in space [1][2][3][4][5] (for the classical version of time crystals, including topologically protected systems, see [6][7][8][9][10][11]). A crystalline structure in time is related to the periodic dynamics of a system.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the Skyrme model in flat spaces, it was well known that if one includes a too large isospin chemical potential then the Skyrmion becomes unstable. However, only very recently in[34] it was derived an analytic formula for this critical chemical potential.…”
mentioning
confidence: 99%